The Effect of Marketing Costs and Product Prices on Increase in Sales At Syanum Coffee Aceh Tamiang - Ardhinur, Ardhinur; M. Ikhsan Harahap; Tri Inda Fadhila Rahma (International Journal of Community Engagement Payungi, 2025)
This study employs a quantitative method with linear regression analysis to investigate how marketing costs and product prices influence sales growth at Syanum Coffee in Aceh Tamiang. The independent variables consist of marketing costs and product prices. The dependent variable in this study is total sales obtained from sales over the past 36 months. With a significance value of 0.000 (p < 0.05), the analysis strongly suggests that increased marketing expenditures lead to significant sales growth. Furthermore, product pricing also plays a significant role in influencing sales, as indicated by its 0.000 significance value (p < 0.05). This research recommends that Syanum Coffee continue to optimize marketing budget allocation effectively and consider pricing that is in accordance with consumer purchasing power to improve sales performance sustainably. In addition, the study’s findings reveal that despite a reduction in marketing costs during the observation period, sales continued to increase, suggesting that other indirect factors such as product quality, customer loyalty, or market trends may also contribute to sustained growth. The high R² value of 0.981 confirms that marketing costs and product prices jointly account for the vast majority of sales variation, reinforcing the strategic importance of these variables. By focusing on a local SME context, this study extends previous findings and provides practical implications for small businesses operating in competitive markets. The evidence underlines the value of targeted promotions and adaptive pricing strategies in boosting business resilience and market responsiveness. Ultimately, this research contributes meaningfully to the field of marketing strategy by offering data-driven guidance to decision-makers seeking long-term, sustainable sales growth through cost-efficient and customer-centric approaches.